2006
DOI: 10.1139/z06-019
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interactions of marine sponges

Abstract: Sponges interact with most other organisms in marine systems as competitors, symbionts, hosts of symbionts, consumers, and prey. Considerable creative energy has been required to study and describe the amazing variety of sponge interactions, as sponges can hide symbionts deep inside, rapidly regenerate wounds from grazers, carry on important associations with unculturable microscopic organisms, and otherwise foil attempts to determine how they are interacting with other organisms. This review of sponge interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
320
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(327 citation statements)
references
References 143 publications
(199 reference statements)
2
320
0
5
Order By: Relevance
“…Sediment-incorporation by the sponge can also reduce the necessity of spicule formation (i.e., spiculogenesis) saving energy that can be allocated to other biological demands such as growth, reproduction and competition (Schönberg, 2016). In addition, D. achorata morphology can also occur as a branching form, avoiding sediment accumulation, with relatively high growth rates, that may accelerate the recovery of predation and competition damages (Wulff, 2006). These adaptations to high sediment conditions (e.g., branching morphology, fast growth rates and rapid regeneration) can explain the increased cover of D. anchorata in TSB reefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment-incorporation by the sponge can also reduce the necessity of spicule formation (i.e., spiculogenesis) saving energy that can be allocated to other biological demands such as growth, reproduction and competition (Schönberg, 2016). In addition, D. achorata morphology can also occur as a branching form, avoiding sediment accumulation, with relatively high growth rates, that may accelerate the recovery of predation and competition damages (Wulff, 2006). These adaptations to high sediment conditions (e.g., branching morphology, fast growth rates and rapid regeneration) can explain the increased cover of D. anchorata in TSB reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Within reef environments, generally sponges are better competitors for space than corals (Aerts, 1998;Pawlik, 2011), mostly due to their defense strategies (Wulff, 2006), as secondary metabolites, and overgrow ability (Aerts, 1998;Meurer et al, 2010). Sponges can negatively affect the recruitment and growth of hermatypic corals, as well as other important coral reefs processes (e.g., substrate construction) (Chadwick and Morrow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that gemmulation process may be caused by endogenous factors and specific environmental conditions (physical and chemical parameters of water) [18,19]. Some studies have demonstrated the morphological diversity of S. lacustris growth forms from different water habits, where body shape was appeared as encrusting to digitated, to branched and arborescent according to the life cycle stage and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Functional Morphology of Chaetetid-Type Porifera 3 fact that carbonates containing domical and columnar chaetetids are also low in siliciclastics led West and rotH (1991) to suggest that these chaetetids might have contained some photosynthesizing symbionts like zooxanthellae and competed with the algae for space. Supporting this suggestion is the reported association between autotrophs and bacteria within marine sponges (Wulff, 2006). erWin and tHacker (2006) reported photosymbionts in reef sponges, and Hill, lopez, and Harriott (2006) reported sponge-specific cyanobacterial and other bacterial symbionts in Caribbean sponges.…”
Section: External Features Growth Formmentioning
confidence: 93%